Continuous catalytic upgrading of ethanol to n-butanol over Cu–CeO2/AC catalysts. Issue 95 (24th October 2016) - Jiang, Dahao; Wu, Xianyuan; Mao, Jun; Ni, Jun; Li, Xiaonian
Abstract : Cu–CeO2 /AC catalysts exhibited the highest n -butanol yields (21.6% and nearly 20%) under mild reaction conditions in batch and fixed-bed reactors, respectively, which could be ascribed to the synergy of Cu, CeO2 and the activated carbon support. Abstract : Cu–CeO2 /AC catalysts exhibited extraordinary catalytic performance in the upgradation of ethanol to n -butanol. To the best of our knowledge, this is the first report that the highest n -butanol yields of 21.6% and nearly 20% could be achieved over heterogeneous catalysts under mild reaction conditions in batch and fixed-bed reactors, respectively. The high catalytic activity, selectivity and stability of these catalysts could be ascribed to the synergy of Cu, CeO2 and the activated carbon support.